2020
DOI: 10.1371/journal.pone.0235426
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic mapping identifies two genetic variants in the MC1R gene for coat colour variation in Chinese Tan sheep

Abstract: Coat colour is one of the most important economic traits of sheep and is mainly used for breed identification and characterization. This trait is determined by the biochemical function, availability and distribution of phaeomelanin and eumelanin pigments. In our study, we conducted a genome-wide association study to identify candidate genes and genetic variants associated with coat colour in 75 Chinese Tan sheep using the ovine 600K SNP BeadChip. Accordingly, we identified two significant SNPs (rs409651063 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Moreover, a GWAS using the OvineSNP600K Beadchip was performed on 75 Chinese Tan sheep individuals (29 black-headed and 46 white-coated; see Additional file 1 : Fig. S4), which revealed two significant SNPs ( rs409651063 and rs408511664 ) in MC1R that were associated with coat color development [ 89 ]. Further information from previous studies on the sheep MC1R gene is shown in Additional file 2 : Table S9.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a GWAS using the OvineSNP600K Beadchip was performed on 75 Chinese Tan sheep individuals (29 black-headed and 46 white-coated; see Additional file 1 : Fig. S4), which revealed two significant SNPs ( rs409651063 and rs408511664 ) in MC1R that were associated with coat color development [ 89 ]. Further information from previous studies on the sheep MC1R gene is shown in Additional file 2 : Table S9.…”
Section: Main Textmentioning
confidence: 99%
“…Table S9. Additional genetic studies on sheep coat color phenotype: The MC1R gene [89,302,[304][305][306][307][308][309]. Table S10.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…For practical reasons, research on animal coloration has continued and flourished mainly on humans [3][4][5] and model systems (i.e. mice [6,7], or domestic animals [8,9]), and has been more recently extended to non-model species, with a handful of studies on birds [10,11], mammals [12,13], butterflies [14] and amphibians [15]. Moreover, many of these studies took advantage of color traits exhibiting relatively simple discrete variation and inheritance patterns thus often contrasting clearly distinctive (eco)morphs [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Other genes associated with adaptability to temperature changes have been found in sheep and goats, including HSP70, which is a set of heat shock protein genes that defend the animals from overheating, and the ENOX2 gene, which has been found in goats susceptible to heat stress [10,11]. Other polymorphic genes, including MCIR, ASIP, and TYRP1, have been observed in different sheep species and are related to wool color, which controls the rate of heat absorption [12]. Accordingly, ruminants' capability to endure, develop, and produce in harsh climates is responsible for their adaptation to different climates.…”
Section: Introductionmentioning
confidence: 99%